Factors associated with acceptance of HIV testing among adolescents in the city of Johannesburg South Africa - Longolongo, Raymond Kibonge (My University, 2020)
Background: Adolescents have emerged as an important group affected by the Human Immunodeficiency Virus(HIV) infection. Key to decreasing the HIV incidence in this population is HIV counselling and testing (HCT), particularly in countries with high prevalence such as South Africa (SA). Although there is data related to the HCT uptake and factors which influence rural SA adolescents’ decision to undergo HCT, there is limited data available for urban SA adolescents. This information has implications related to the design of HCT interventions targeting adolescents in urban SA settings. This study aimed to determine factors of low HCT uptake amongst adolescents in the city of Johannesburg, SA. Methods: This was a secondary analysis of data from a survey of adolescents (aged 10-19 years old), which was conducted by a non-governmental organisation in two regions of Johannesburg, SA during 2016 and 2017. The proportion of adolescents who subsequently consented to HCT (community-based outreach) was determined. Data from the survey was analysed with bivariate and multivariate statistical methods to identify factors associated with the decision to undergo HCT. Results: The final study sample consisted of 114 sexually active adolescents. A total of 97 out of the 114 study participants (85.1%) had subsequently consented to undergo HCT. In the multivariate model (adjusted for age), two factors were independently associated with HCT uptake: lack of support from friends and family (Odds ratio (OR): 0.20, 95% CI: 0.05-0.80, p=0.023) and belief that one was at risk of HIV infection (OR: 3.93, 95% CI: 1.03-14.96, p=0.045). Conclusions: The level of HCT uptake amongst adolescents in this study was 85%. Lack of support was associated with a lower odds of consenting to HCT, whereas selfperceived risk of HIV infection associated with higher odds of consenting to HCT. The findings of this study require confirmation, but nonetheless provide information which can be useful for designing future HCT campaigns in this urban setting.
A research report submitted to the faculty of health sciences in partial fulfilment of the requirement for the degree of Master of Science in Epidemiology in the field of Infectious Diseases at the University of the Witwatersrand, Johannesburg, 2020